Depth Study of User Purchase Influencing Factors in Platform E-commerce under the Background of Big Data and AI - Tang, Na; Han, Yixuan; Wu, Yanlin; Sun, Fuli; Lai, Xinyue; Huang, Bingyan (LPPM STIKI Malang, 2024)
Taking Taobao as a typical platform e-commerce, this study is devoted to exploring how big data and artificial intelligence technology can empower platform e-commerce and affect users' purchase intention. This paper adopts the empirical research method, collects data through online questionnaire, uses spss26 for regression analysis, and adopts the gradient lifting algorithm of machine learning model for data verification. The research results show that marketing activities such as